An Empirical Analysis Of Resistance To Organisational Change In Merging Banks - Abdul Muthalib, Fadilah (2001)
This study investigates the factors that cause resistance to change in merging banks. The factors that cause resistance to change are conformity to norms and culture, uncertainty regarding change, loss of existing benefits and threats to position power.